Preferensi Polen Sumber Pakan Lebah Kelulut pada Tiga Tipe Penggunaan Lahan di Pulau Lombok - Septiantina Riendriasari; Anita Apriliani Dwi Rahayu (Jurnal Ilmu Kehutanan, 2022)
The success of stingless beekeeping was determined by site suitability and the availability of floral sources. Bee forage was also an important requirement used to improve the qualities and quantities of its products. Information about specific forage plants in different land uses was needed to make the plants sufficient. Therefore, this study aimed to examine forage preference for stingless bees in different land use areas. The location used was categorized into three types, namely agroecosystems, forests, and settlements. The pollen samples were analyzed with acetolysis and then identified. The results showed four species of stingless bees, namely Tetragonula fuscobalteata, T. laeviceps, and T. clypearis, as well as Heterotrigona erythrogastra. T. fuscobalteata was mostly cultivated in the settlements, T. laeviceps and T. clypearis were cultivated in the agroecosystems, while H. erythrogastra was mostly found near the forest. The identification of pollen showed that the favorite feed plants of Tetragonula were Bromeliaceae and Cyperaceae, while the forage preference for H. erythrogastra was Rubiaceae. The Principal Component Analysis revealed that the bees' preference was influenced by the availability of forage sources. Based on the results, stingless bees did not have specific forage plants, but foraging was often carried out to provide an abundance.